Resolution for The Development of Contemporary Islamic Boarding Schools in Responding to The Challenges of The Digital Era (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
Abstract: Islamic boarding schools (pondok pesantren), as educational institutions that have played a significant role in the history of education in Indonesia, are currently facing various challenges arising from the rapid development of the digital era. Advances in information technology, cultural globalization, changing communication patterns, and the increasing demand for 21st-century competencies require pesantren to adapt while maintaining the Islamic values that form their identity. This article aims to analyze the challenges faced by contemporary pesantren and to formulate development strategies that can be implemented to address these challenges. The study employs a library research method by examining various literature related to pesantren education and digital transformation. The findings indicate that the development of pesantren requires the integration of digital technology into learning processes, the enhancement of digital literacy, the strengthening of curricula that combine Islamic studies with modern sciences, the improvement of human resource quality, the reinforcement of religious moderation, and the development of technology-based economic independence. Furthermore, a culture of research and innovation needs to be fostered to enhance the competitiveness of pesantren. Sustainable transformation will enable pesantren to remain relevant, excellent, and competitive in the future.
Keywords: Islamic Boarding School (Pondok Pesantren); Digital Era; Islamic Education Transformation; Digital Literacy; Pesantren Development.